A gene expression signature for high-risk multiple myeloma - Kuiper, Rowan; Goldschmidt, Hartmut (Leukemia, 2012)
There is a strong need to better predict the survival of patients with newly diagnosed multiple myeloma (MM). As gene expression profiles (GEPs) reflect the biology of MM in individual patients, we built a prognostic signature based on GEPs. GEPs obtained from newly diagnosed MM patients included in the HOVON65/GMMG-HD4 trial (n=290) were used as training data. Using this set, a prognostic signature of 92 genes (EMC-92-gene signature) was generated by supervised principal component analysis combined with simulated annealing. Performance of the EMC-92-gene signature was confirmed in independent validation sets of newly diagnosed (total therapy (TT)2, n=351; TT3, n=142; MRC-IX, n=247) and relapsed patients (APEX, n=264). In all the sets, patients defined as high-risk by the EMC-92-gene signature show a clearly reduced overall survival (OS) with a hazard ratio (HR) of 3.40 (95% confidence interval (CI): 2.19-5.29) for the TT2 study, 5.23 (95% CI: 2.46-11.13) for the TT3 study, 2.38 (95% CI: 1.65-3.43) for the MRC-IX study and 3.01 (95% CI: 2.06-4.39) for the APEX study (P<0.0001 in all studies). In multivariate analyses this signature was proven to be independent of the currently used prognostic factors. The EMC-92-gene signature is better or comparable to previously published signatures. This signature contributes to risk assessment in clinical trials and could provide a tool for treatment choices in high-risk MM patients.